The Global Classroom in Action: Thirty Years of International Studies at the University of Technology Sydney - Paul Allatson (PORTAL: Journal of Multidisciplinary International Studies)
2024 marks a significant milestone for the Bachelor of Arts in International Studies (BAIS) and its successor, the Bachelor of International Studies (BIS), at the University of Technology Sydney (UTS): 30 years of pioneering global education and the fostering of international and transcultural understanding. To commemorate this anniversary in this issue of Portal: Journal of Multidisciplinary International Studies, a selection of academic staff, past and present, who have contributed to the program, share their memories and insights through short essays and reflective pieces. This initiative seeks to honour the diverse experiences and pedagogical innovations that have shaped the program’s success over the decades. It also aims to explain the inevitable evolution of international studies at UTS in the wake of the global pandemic whose associated travel restrictions forced a rethink of how UTS might better deliver international studies with an array of new “internationalised/ising” experiences some of which start right here, where we are now.